Cluster Analysis for the Relationship between Mathematical Communication Ability and Student’s Problem-Solving Ability - Dwitasari, Devi; Noor, Nik Nur Aimee Widad BT Nik Mohammed (Lembaga Penelitian dan Pengembangan Matematika dan Statistika Terapan Indonesia, PT Anugrah Teknologi Kecerdasan Buatan PT Anugrah Teknologi Kecerdasan Buatan, 2024)
This study aims to determine how mathematical communication ability with students' problem-solving ability. This research uses a quantitative approach with correlational methods and cluster analysis. The research was conducted at SMPN 1 Rengasdengklok with the population being all class VIII in the 2023/2024 school year. Determination of the sample in this study using purposive sampling technique, where researchers took samples based on the results of consideration to students who had obtained statistical material. Taking the number of samples in this study using the Slovin formula, 83 samples were used in the study. Data collection techniques in this study used mathematical communication ability test instruments and problem-solving skills. This study uses the k-means clustering analysis technique to divide the data into high, medium, and low categories. And analyzed using the Spearman rank correlation test to determine the level of relationship between the entire sample and each cluster. The results of this study show that in cluster 1 30 students have high ability, in cluster 2 as many as 37 students have medium ability, and in cluster 3 as many as 16 students have low ability. The correlation test results for the entire sample have a significant relationship with a contribution of 37.45%. The correlation test results for cluster 1 do not have a significant relationship with a contribution of 7.4%. The correlation test results in cluster 2 have an insignificant relationship with a contribution of 2.2%. The correlation test results in cluster 3 have an insignificant and unidirectional relationship.